(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2014)
Laboratory investigations were performed in order to assess the effectiveness of three types of inhibitors, calcium nitrite, ethanolamine and Sika ferro gard 901(commercial inhibitor) with 1%, 2% and 3%concentration by weight of cement for each inhibitor to retarding corrosion of steel embedded in concrete. Concrete specimens were used to assess the effects of corrosion inhibitors on the compressive and tensile strength of concrete and corrosion of reinforcement.Some of the specimens were subjected to wetting and drying cycles and reinforcement corrosion was evaluated by measuring corrosion potentials and corrosion current density. Other concrete specimens were immersed in the salt (Cl-+So3-2) solution and reinforcement corrosion was accelerated by impressing an anodic potential of +12 V from a DC power supply and measuring the time-to-cracking of the concrete specimens.The results indicated that the concrete specimens incorporated corrosion inhibitors of calcium nitrite and Sika ferro gard 901 did not adversely affect the compressive and tensile strength of concrete. Furthermore, the time-to-cracking in specimens contains those two inhibitors (calcium nitrite and Sika ferro gard 901) were higher. Two percent of calcium nitrite followed by three percent of Sika ferro gard 901 were efficient in delaying the initiation of reinforcement corrosion and reducing the rate of reinforcement corrosion current density in the concrete specimens, while all the percentages of ethanolamine corrosion inhibitor were ineffective to delay corrosion of the rebar under the conditions of the study and it’s adversely affect the strength.